1979
DOI: 10.1111/j.0954-6820.1979.tb06029.x
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Treatment with Levomepromazine in Acute Myocardial Infarction

Abstract: ABSTRACT. The efficacy of a non‐narcotic analgesic is evaluated in a double‐blind randomized series of patients with acute myocardial infarction (AMI). Levomepromazine or pethidine were given in 328 consecutive cases to 316 patients within 24 hours after the onset of symptoms. Levomepromazine, 12.5 mg, appeared as effective as pethidine, 50 mg, in the alleviation of pain, though the initial dose had to be higher. Nausea and vomiting were half as frequent in the levomepromazine group as in the pethidine group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…A couple of studies in the 1960es and 1970es reported levomepromazine to be effective in treatment of pain in cancer patients [72]–[74], and there even seems to be an accepted conversion scale for morphine to levomepromazine of 1.5:1 [75]. Our review included one case report published in 1987, and one study from 1985 underlining these previous findings [41,59], but regrettably there seems to be absolutely no later published research on the use of levomepromazine for pain in palliative care or cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…A couple of studies in the 1960es and 1970es reported levomepromazine to be effective in treatment of pain in cancer patients [72]–[74], and there even seems to be an accepted conversion scale for morphine to levomepromazine of 1.5:1 [75]. Our review included one case report published in 1987, and one study from 1985 underlining these previous findings [41,59], but regrettably there seems to be absolutely no later published research on the use of levomepromazine for pain in palliative care or cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Many antipsychotics have 5HT(2A) antagonistic activity, and 5HT(2A) antagonists have been shown to have a strong antiplatelet-aggregation effect in vitro,44 to reduce coronary thrombosis in animal models,45 46 and to reduce cardiovascular mortality by 23% in a large RCT 47. In the study presented here, however, we did not find a protective effect of strong 5HT(2A) antagonists (OR 0.8, CI 0.6 to 1.1).…”
Section: Discussionmentioning
confidence: 99%
“…Also, ACS may present with atypical symptoms in these patients. Antipsychotics are known to reduce the pain accompanying an ACS, increasing the risk that the physician misinterprets the signs of ACS 47 57. Finally, it is possible that most patients with an ACS were already identified as being at risk for cardiovascular disease (table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Only one trial included more than 200 participants. 23 Study Design. Eight of the 11 included studies had a parallel design, and three had a crossover design.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…25 Two trials simply reported on the mere occurrence of pain. 23,27 Study Methods. All 11 included studies were conducted in a double-blind fashion.…”
Section: Description Of Studiesmentioning
confidence: 99%